The wounded animal : J.M. Coetzee and the difficulty of reality in literature and philosophy - Mulhall, Stephen, 1962- (Princeton University Press, 2009)
Taking a work by J.M. Coetzee as an example, this volume explores the way both literature and philosophy seek - and fail - to represent reality. Stephen Mulhall examines Coetzee's 'Elizabeth Costello', which deals with the moral status of animals.